2022
DOI: 10.3390/healthcare10020217
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability on Serious Adverse Events of First-Line Bevacizumab and Cetuximab for RAS Wild-Type Metastatic Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Proper medication management is crucial in metastatic colorectal cancer because of its substantially low survival rate. There has been advancing evidence on the efficacy of the two most prescribed targeted agents (bevacizumab and cetuximab); however, comprehensive analyses on their safety are limited. This study aims to comprehensively assess the clinical safety of first-line bevacizumab and cetuximab-based chemotherapy in unresectable RAS wild-type metastatic colorectal cancer patients and to provide guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…Similar to the results from a previous meta-analysis on the tolerability on SAE of first-line bevacizumab and cetuximab for RAS wild-type metastatic CRC patients [ 37 ], the highest risk of serious HTN was observed in bevacizumab-based chemotherapy (RR 1.00; reference) over cetuximab- (RR 0.05; 95% CI 0.00–0.85) and panitumumab-based chemotherapy (RR 0.07; 95% CI 0.01–0.55); the RR of HTN was insignificant between second-line bevacizumab- and panitumumab-based chemotherapy. However, caution is advised with the interpretation of safety assessment results of second-line targeted treatment as it was evaluated with only one RCT [ 32 ], which demonstrated 4 and 0 cases of serious HTN (Grade 3 or 4 per CTCAE) in patients on bevacizumab- and cetuximab-based chemotherapy, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to the results from a previous meta-analysis on the tolerability on SAE of first-line bevacizumab and cetuximab for RAS wild-type metastatic CRC patients [ 37 ], the highest risk of serious HTN was observed in bevacizumab-based chemotherapy (RR 1.00; reference) over cetuximab- (RR 0.05; 95% CI 0.00–0.85) and panitumumab-based chemotherapy (RR 0.07; 95% CI 0.01–0.55); the RR of HTN was insignificant between second-line bevacizumab- and panitumumab-based chemotherapy. However, caution is advised with the interpretation of safety assessment results of second-line targeted treatment as it was evaluated with only one RCT [ 32 ], which demonstrated 4 and 0 cases of serious HTN (Grade 3 or 4 per CTCAE) in patients on bevacizumab- and cetuximab-based chemotherapy, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Skin toxicities, including acneiform skin rash and nail disorders, are well-known AEs of EGFR inhibitors [ 35 ], and previous meta-analysis from our research group also suggested higher risk of skin toxicities with cetuximab over bevacizumab [ 37 ]. This study revealed a significantly greater risk of serious dermatitis or paronychia with EGFR inhibitors, cetuximab and panitumumab.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the absenteeism of the patients and their companions from work in this group was more than that in the group under treatment with FOLFOX6+Cetuximab. Furthermore, due to the fact that the side effects of FOLFOX6+Bevacizumab are usually greater and more severe than FOLFOX6+Cetuximab, and since chemotherapy by Bevacizumab increases the risk of cardiovascular diseases such as increased blood pressure and irregular heartbeat, 57 the cost of changes in the home environment for the adaptation of these patients was higher (approximately 2.5 times). These could have caused an increase in direct non-medical and indirect costs in the group receiving FOLFOX6+Bevacizumab.…”
Section: Discussionmentioning
confidence: 99%